The Efficacy and Safety of Sintilimab Combined With Nab-Paclitaxel as a Second-Line Treatment for Advanced or Metastatic Gastric Cancer and Gastroesophageal Junction Cancer - Wang, Jianzheng; He, Yunduan; Zhang, Baiwen; Lv, Huifang; Nie, Caiyun; Chen, Beibei; Xu, Weifeng; Zhao, Jing; Cheng, Xiaojiao; Li, Qingli; Tu, Shuiping; Chen, Xiaobing (Frontiers in Oncology, 2022)
Background: Unresectable advanced or recurrent gastric cancer patients have a poor prognosis. PD-1 monotherapy regimen and PD-1 combined chemotherapy regimen have become the standard third- and first-line treatment for advanced gastric cancer, respectively. However, the status of immune checkpoint inhibitors in the second-line treatment for advanced gastric cancer has not been established. The combination of chemotherapy and anti-PD-1 antibody has been demonstrated to have a synergistic effect. In this study, we aimed to evaluate the efficacy and safety of sintilimab combined with nab-paclitaxel in the second-line treatment for advanced gastric cancer (GC)/ gastroesophageal junction (GEJ) cancer patients. Patients and Methods: We retrospectively analyzed patients with advanced GC/GEJ cancer that progressed after first-line systemic therapies with sintilimab combined with nab-paclitaxel from April 1, 2019 to December 31, 2021. The primary endpoint was progression-free survival (PFS). The secondary endpoints included objective response rate (ORR), disease control rate (DCR), and safety. Results: Thirty-nine patients were enrolled and eligible for response assessment. Complete response (CR) was not observed, 15 patients achieved partial response (PR), 16 patients had stable disease (SD) and 9 patients had progressive disease (PD). The ORR and DCR were 15 (38.5%) and 31 (79.5%), respectively. Median PFS was 5.4 months (95%CI: 3.072-7.728). PFSs between different subgroups were analyzed. The results showed that gender, age, Human epidermal growth factor receptors 2 (HER2) status, PD-L1 expression, primary tumor site and chemotherapy cycles had no significant effect on PFS. Most of the adverse events (AEs) were of grade 1-2 and manageable. The common treatment-related adverse events of grade 3 or 4 included anemia (12.8%), neutropenia (12.8%), leukopenia (10.3%), hand-foot syndrome (7.7%), thrombocytopenia (7.7%). The potential immune-related adverse events (irAEs) were grade 1 pneumonia (1 pts [2.6%]) and grade 4 hepatitis (1 pts [2.6%]). There were no treatment-related deaths. Conclusion: These results indicate that sintilimab combined with nab-paclitaxel exhibits good anti-tumor activity and an acceptable safety profile as a second-line treatment for advanced or metastatic gastric cancer. These results warrant further investigation and evaluation to identify patients who can benefit more from the combined treatment strategy.